2017
DOI: 10.1002/ppsc.201600346
|View full text |Cite
|
Sign up to set email alerts
|

Defluorination of Fluorographene Oxide via Solvent Interactions

Abstract: CommuniCation(1 of 7) 1600346 F in FG cannot stabilize the FG-ammonia structure. [4] Hence, it is important to develop a method for the large-scale controlled fluorination/defluorination of graphene/FG. [15,16] Conventional F doping level control in graphene relies on the tuning the amount of reagents or flow and time of the fluorination gases and process. [11,17] Mechanical exfoliation of graphite fluoride is the first method reported for FG synthesis while chemical exfoliation of various types of fluorograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…23 Recently, the authors have demonstrated that the interactions between polar solvents and C-F bond in FG are highly crucial for the solvent assisted defluorination, and even moderately polar solvents such as tetrahydrofuran (THF) can interact with FGO to remove C-F bonds in a day or two without any extensive sonication. 40 This method also proves that other oxygen functionalities are kept intact even after 30 days of THF treatment indicating that the reaction is quite selective. Hence this can be considered as an important step toward the development of controllably fluorinated graphene/graphene oxide based devices and sensors.…”
Section: Fluorination Of Graphene-synthesis and Control Of Fluorinementioning
confidence: 79%
See 3 more Smart Citations
“…23 Recently, the authors have demonstrated that the interactions between polar solvents and C-F bond in FG are highly crucial for the solvent assisted defluorination, and even moderately polar solvents such as tetrahydrofuran (THF) can interact with FGO to remove C-F bonds in a day or two without any extensive sonication. 40 This method also proves that other oxygen functionalities are kept intact even after 30 days of THF treatment indicating that the reaction is quite selective. Hence this can be considered as an important step toward the development of controllably fluorinated graphene/graphene oxide based devices and sensors.…”
Section: Fluorination Of Graphene-synthesis and Control Of Fluorinementioning
confidence: 79%
“…8). 40 It is found that the solvent assisted interactions can reduce the F content in FGO, and this has a significant role in the response of the FG based conductometric sensor. Low F containing sample (30 days treated FGO) has the highest response indicating that changes in the conductivity (along with adsorption properties as observed from the DFT studies) of FGO upon defluorination and its effects in the sensing response.…”
Section: Fluorographene As a Sensing Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…The G band (in the region of 1500-1600 cm À1 ) arises from the rst order scattering of the E 2g phonon at the Brillouin zone center, resulting from the bond stretching of sp 2 carbon lattice pairs in both rings and chains. 44,45 A strong peak located at 531 cm À1 is typically assigned to NCA-LTH. 9 It is known that the integrated intensity ratio of the bands (I D /I G ) is used to qualitatively analyze the structural defects and disorder of graphite materials.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%